Mastering Sustainability in Supply Chains - Lazarević, Mirjana (University of Maribor Press, 2026)
The higher education textbook "Mastering Sustainability in Supply Chains" is a comprehensive guide designed to support sustainability and the greening of logistics processes. It emphasizes modern approaches and concepts for environmental protection and minimizing environmental impacts while simultaneously increasing added value and productivity. The textbook covers the use of environmental assessment tools and the establishment of circular supply chains. An interdisciplinary approach integrates knowledge from various fields, including environmental management, eco-friendly product design, carbon footprint assessment, green logistics, energy supply, and the application of practical knowledge beyond logistics and supply chains. Readers are equipped with practical skills to enhance sustainability, productivity, and process transparency. The textbook covers topics such as: 1) Climate change, 2) Environmental assessment – carbon footprint, 3) Life cycle assessment (LCA), 4) Circular economy, 5) Sustainable energy self-sufficiency, 6) Eco-design. The entire content is aimed at strengthening sustainability competencies, which are crucial for the green transition of logistics companies and increasing the resilience of supply chains.